Risk factors and diagnostic significance of the N-terminal pro-brain natriuretic peptide as a marker in patients with acute decompensated heart failure and diabetic kidney disease - N. A. Koziolova; A. S. Veklich (Российский кардиологический журнал, 2021)
Aim. To assess the risk factors and diagnostic significance of the N-terminal probrain natriuretic peptide (NT-proBNP) in patients with acute decompensated heart failure (ADHF) and diabetic kidney disease (DKD).Material and methods. A total of 125 patients with ADHF and type 2 diabetes (T2D) were examined. They were divided into 2 groups depending on the presence/ absence of chronic kidney disease (CKD). The first group consisted of 43 (34,4%) patients with DKD, the second — 82 (65,6%) without CKD. The inclusion criterion was the presence of ADHF and T2D. There were following exclusion criteria: cardiogenic shock, pulmonary edema, acute thromboembolic events, type 1 diabetes, prediabetes, acute coronary syndrome, stroke, prior transient ischemic attack (<1 month old), dissecting aneurysm or aortic dissection, acute valvular disorders, major surgery (<1 month old), cardiac trauma, infective endocarditis, acute hepatitis and cirrhosis, terminal CKD, alcohol abuse, non-cardiac edema, cancer, dementia and mental disorders.Results. With the development of a hypertensive crisis and an increase in diastolic blood pressure >100 mm Hg, the odds ratio (OR) and the relative risk (RR) of ADHF in patients with DKD increases by 5,1 and 4,5 times, 2,5 and 1,8 times, respectively. In the presence of grade III-V premature ventricular contractions, OR and RR of ADHF in patients with DKD were 2,6 and 1,9, respectively. OR and RR of ADHD in patients with DKD and prior stroke or transient ischemic attack were 3,8 and 3,2, respectively. Verification of anemia at a hemoglobin level of 5 mmol/l, the OR of ADHF in patients with DKD increases by 3,7 times, the OR — by 2,3 times. The NT-proBNP >1289 pg/ml is diagnostic for verifying ADHF in DKD patients with the sensitivity of 64,3% and specificity of 93,3%.Conclusion. Every third patient with ADHF and T2D is diagnosed with DKD. A certain range of risk factors for the development of ADHF in patients with DKD has been identified. As the glomerular filtration rate (GFR) decreases, the NT-proBNP level increases. With a decrease in GFR of 60 ml/min/1,73 m2 in patients with T2D, the diagnostic value of NT-proBNP >1289 pg/ml should be considered to verify ADF.